2019
DOI: 10.1101/558783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic checkpoint deficiency during cell cycle re-entry from quiescence

Abstract: The authors find that human cells re-entering the cell cycle from quiescence have both an impaired p53-dependent DNA replication origin licensing checkpoint and slow origin licensing. This combination makes every first S phase underlicensed and hypersensitive to replication stress. ABSTRACTTo maintain tissue homeostasis, cells transition between cell cycle quiescence and proliferation. An essential G1 process is Minichromosome Maintenance complex (MCM) loading at DNA replication origins to prepare for S phase,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
(92 reference statements)
1
6
0
2
Order By: Relevance
“…In this sense, various cell synchronization methods have been criticized for creating an artificial situation [ 10 ]. Indeed, recent evidence indicates that even a pause before initiating the cell cycle (i.e., entry to quiescence) will affect how the following S-phase is performed [ 11 ]. A prime example of a cell cycle pause is a DNA damage checkpoint.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, various cell synchronization methods have been criticized for creating an artificial situation [ 10 ]. Indeed, recent evidence indicates that even a pause before initiating the cell cycle (i.e., entry to quiescence) will affect how the following S-phase is performed [ 11 ]. A prime example of a cell cycle pause is a DNA damage checkpoint.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high p21 is also an indirect consequence of G1 arrest, since p21 is degraded in S phase cells and stable in G1 . We recently found that cells re‐entering the cell cycle from quiescence have an impaired licensing checkpoint . This natural checkpoint deficiency may provide a unique avenue to dissect the pathway connecting licensing to S phase entry.…”
Section: G1: Preparing Dna For S Phasementioning
confidence: 99%
“…When the checkpoint regulators are depleted or mutated, the cells can proceed prematurely into S phase, albeit with a higher risk of incomplete replication. Indeed, in nontransformed mammalian cell lines, manipulations that inhibit origin licensing result in a longer G1 phase and low CDK2 activity . Interestingly, the same manipulations in transformed cell lines do not affect G1 length or CDK2 activity, and cells instead proceed into S phase with considerably less than their typical amount of licensed origins.…”
Section: G1: Preparing Dna For S Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Απορρύθμιση της αδειοδότησης της αντιγραφής είτε μέσω αποσιώπησης είτε μέσω υπερέκφρασης παραγόντων του προαντιγραφικού συμπλόκου θα μπορούσε να οδηγήσει σε αντιγραφικό στρες, γονιδιωματική αστάθεια και κυτταρικό θάνατο, ειδικότερα στα καρκινικά κύτταρα. Πιο συγκεκριμένα, αποσιώπηση της έκφρασης του CDT1 είτε υπερέκφραση της Geminin έχει δειχθεί ότι προκαλεί παύση του κυτταρικού κύκλου στην G1 φάση στα φυσιολογικά κύτταρα, ενώ ενεργοποιεί την διαδικασία της απόπτωσης στα καρκινικά κύτταρα (Shreeram et al, 2002;Nevis et al, 2009;Matson et al, 2017;Matson et al, 2019). Σε φυσιολογικά κύτταρα, έπειτα από περιορισμένη αδειοδότηση των αφετηριών της αντιγραφής, ενεργοποιείται το σημείο ελέγχου της αδειοδότησης, το οποίο προκαλεί παύση στη G1 φάση έως ότου ο κατάλληλος αριθμός των αφετηριών της αντιγραφής αδειοδοτηθεί (ΜcIntosh and Blow, 2012).…”
Section: συνθετικές χημικές ενώσεις με πιθανή αντικαρκινική δράση μέσω αναστολής της αλληλεπίδρασης των Cdt1-gemininunclassified